An early-strength alkali-activated all-solid waste-based regenerated mortar and a preparation method thereof

Through the activity improvement and dense pores of the regenerative powder and regenerative aggregate, prepare the early strong alkali to stimulate the full -fixed waste -based recycled mortar, and solve the poor activity of the regenerative powder in the existing technology The problem realizes the effective reuse of the early strength characteristics and the solid waste of the building.

CN116514510BActive Publication Date: 2025-01-28YANGZHOU UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310452528.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-25
Publication Date
2025-01-28
Estimated Expiration
2043-04-25

AI Technical Summary

Technical Problem

In the prior art, the regenerated powder has poor activity, high porosity and water absorption rate of regenerated aggregates, resulting in the inability to perform bulk recycling and reuse in alkali-activated gelling materials.

Method used

By improving activity and dense pores, the regenerative powder and regeneration aggregate are processed, including steps such as wastewater spraying, carbonized maintenance and thermal activation of concrete sedimentation tanks to prepare early -strong alkali stimulating full -solid waste -based recycled mortar.

Benefits of technology

It significantly improves the performance of recycled powder and recycled aggregate, realizes the excellent characteristics of early strength, and promotes the good application of solid waste in the building, reducing its dependence on traditional materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention belongs to the technical field of recycling and reuse of construction solid waste, and in particular discloses an early-strength alkali-activated all-solid waste-based regenerated mortar, and a preparation method thereof. The alkali-activated all-solid waste-based regenerated mortar, on the one hand, greatly improves its activity by successively subjecting the regenerated powder to the treatments of concrete sedimentation tank wastewater spraying-carbonization curing-thermal activation; on the other hand, by successively subjecting the regenerated fine aggregate to the treatments of concrete sedimentation tank wastewater spraying-carbonization curing, greatly densifies its structure and reduces its porosity. Based on these two optimization treatments, a large amount of construction solid waste resource-based regenerated powder can be consumed, reducing the dependence of alkali-activated materials on traditional materials, and also realizing the recycling of wastewater from mixing station sedimentation tanks, so that large amounts of construction solid and liquid waste can be well applied to the production of alkali-activated all-solid waste regenerated mortar, and achieving excellent early strength characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of construction solid waste recycling and reuse, and specifically relates to an early-strength alkali-activated all-solid waste-based regenerated mortar, and a preparation method thereof. Background Art

[0002] Alkali-activated cementitious material is a new type of green cementitious material. Compared with traditional cement-based materials, it has a simpler preparation process, lower energy consumption and lower CO2 emissions. However, the shortage of supply and continued high prices of traditional auxiliary cementitious materials such as slag and fly ash have restricted the wider engineering application of alkali-activated slag / fly ash concrete.

[0003] Using recycled powder to prepare alkali-activated materials has good social and economic effects. However, the activity of recycled powder is low, resulting in poor performance of the alkali-activated materials prepared therefrom, and good application effects cannot be achieved.

[0004] The performance of recycled aggregate is also inferior to that of natural aggregate. At present, relevant scholars have modified and improved the performance of recycled aggregate through CO2 mineralization to strengthen building materials products, but the porosity and water absorption rate are still higher than natural aggregate after direct carbonization treatment. This is because the carbonization degree and depth of the old mortar on the surface of recycled aggregate are still limited, and the single CO2 mineralization strengthening effect is still limited.

[0005] Therefore, although bulk construction solid waste such as recycled powder and recycled aggregate can be recycled and reused in alkali-activated cementitious materials, due to their respective performance defects, they still need to be continuously improved and processed to achieve good reuse effects. Summary of the invention

[0006] In order to solve the problem in the prior art that the recycled powder has poor activity, the recycled aggregate has high porosity and water absorption, and thus cannot be recycled and reused in large quantities in alkali-activated cementitious materials, the present invention respectively treats the recycled powder and the recycled aggregate to enhance their activity and compact their pores, and based on the treated two, provides an early-strength alkali-activated all-solid waste-based recycled mortar.

[0007] The present invention specifically adopts the following technical solutions:

[0008] An early-strength alkali-activated all-solid waste-based regenerated mortar, comprising the following components mixed evenly:

[0009]

[0010] Among them, the activated regenerated powder is a powder obtained by spraying and soaking the regenerated powder with wastewater from a concrete sedimentation tank, carbonizing and curing it, and then thermally activating it, with a particle size not exceeding 150μm;

[0011] CO2 enhanced recycled fine aggregate is a continuously graded particle with a particle size of 0.15mm to 5mm obtained by spraying and soaking the recycled fine aggregate with wastewater from a concrete sedimentation tank and then carbonizing and curing it.

[0012] In the above-mentioned early-strength alkali-activated all-solid waste-based regeneration mortar of the present invention, on the one hand, the activity of the regenerated powder is greatly improved by successively subjecting it to the treatment of concrete sedimentation tank wastewater spraying-carbonization curing-thermal activation. On the other hand, the structure of the regenerated fine aggregate is greatly compacted and the porosity is reduced by successively subjecting it to the treatment of concrete sedimentation tank wastewater spraying-carbonization curing. Based on these two optimization treatments, the bulk of construction solid waste can be well applied to the production of alkali-activated all-solid waste regeneration mortar, and the excellent characteristics of early strength are achieved.

[0013] Specifically, first, generally speaking, the regenerated powder contains inert substances such as silicon dioxide and calcium carbonate, as well as hydration products such as CSH gel, calcium sulfate and calcium hydroxide. Therefore, after the regenerated powder is sprayed with wastewater from the concrete sedimentation tank, it can fully absorb gas and mineralize to form calcium carbonate in the CO2 atmosphere. Its own CSH gel decomposes into calcium carbonate and silica gel during the carbonization process, and the hydrated calcium sulfoaluminate decomposes into gypsum, calcium carbonate and other silicon-aluminum oxides. The above calcium carbonate decomposes into active CaO (which has the effect of improving activity) after high temperature, and under the action of high temperature, CaO may also react with CSH gel dehydrated phase and other substances to form β-C2S. The C2S produced during the calcination of the regenerated powder presents a certain degree of amorphous state and has a high reactivity. Therefore, the activity of the regenerated powder can be improved by adopting the operation of "spraying wastewater from concrete sedimentation tank-carbonization curing-thermal activation".

[0014] Secondly, after spraying the recycled fine aggregate with wastewater from the concrete sedimentation tank, the recycled fine aggregate can fully absorb the gas and mineralize to form calcium carbonate in the CO2 atmosphere, which compacts the pores of the recycled fine aggregate and greatly reduces its porosity, thereby improving the performance of the recycled fine aggregate. Compared with the general direct carbonization treatment operation in the prior art, the compaction effect is better.

[0015] Furthermore, the recycled powder is prepared from different types of construction waste after demolition of buildings or structures, including one or a mixture of at least two of recycled concrete powder, recycled mortar powder, and recycled paste powder.

[0016] Furthermore, in the preparation of activated regenerated powder, the conditions for carbonization curing are: CO2 purity is not less than 99.9%, CO2 concentration is 10% to 30%, carbonization temperature is 60°C to 100°C, and carbonization time is 0.5h to 1h; the conditions for thermal activation are: thermal activation temperature is 600°C to 800°C, and thermal activation time is 60min to 120min.

[0017] Furthermore, in the preparation of CO2-enhanced recycled fine aggregate, the carbonization curing conditions are: CO2 purity is not less than 99.9%, carbonization pressure is 0.1 bar to 0.4 bar, carbonization temperature is 20±2°C, carbonization time is 20h to 30h, and carbonization relative humidity is not less than 50%.

[0018] Specifically, the wastewater from the concrete sedimentation tank sprayed in the preparation of the activated recycled powder and CO2-enhanced recycled fine aggregate is the untreated wastewater from the commercial concrete sedimentation tank, which is a calcium-rich waste liquid. It is sprayed until the recycled powder and recycled fine aggregate are in a saturated surface dry state before carbonization curing. Using it as a spraying liquid, while processing and optimizing the performance of bulk recycled powder and recycled fine aggregate, it is also a recycling and reuse of this bulk wastewater, reducing pollution and increasing its economic added value.

[0019] Furthermore, the recycled carbon fiber is carbon fiber extracted from waste fibers or waste generated in the process of producing carbon fiber.

[0020] Furthermore, the length of the recycled carbon fiber is 6 mm to 18 mm, the diameter is 7 μm to 12 μm, the tensile strength is 1910 MPa to 2200 MPa, and the elongation at break is 2.85% to 3.43%.

[0021] Furthermore, the alkali activator is selected from any one of potassium water glass, sodium water glass (preferably with a modulus of 1.0 to 1.6), and sodium hydroxide, or a mixture of at least two thereof.

[0022] Furthermore, the water reducing agent may be, for example, sodium lignin sulfonate, the retarder may be, for example, ascorbic acid, the dispersant may be, for example, methyl cellulose, etc., which are not listed here one by one, and those skilled in the art may refer to the conventional selection in alkali-activated mortar.

[0023] Another object of the present invention is to provide a method for preparing the above-mentioned early-strength alkali-activated all-solid waste-based regenerated mortar, which comprises the following steps:

[0024] S1. Preliminarily dispersing the regenerated carbon fiber and the dispersant in part of the water, and then sequentially adding a retarder and an alkali activator thereto for secondary dispersion to obtain a mixed functional component;

[0025] S2. Stir the remaining water with the CO2 enhanced recycled fine aggregate to make the surface of the CO2 enhanced recycled fine aggregate wet;

[0026] S3, mixing the activated regenerated powder with fly ash and phosphogypsum to obtain a mixed powder;

[0027] S4. Fully stir the mixed functional components and the mixed powder, add the moistened CO2-strengthened recycled fine aggregate, add the water reducing agent, mix them thoroughly and evenly, and obtain the early-strength alkali-activated all-solid waste-based recycled mortar.

[0028] In the above step S2, the specific preparation method of CO2 enhanced recycled fine aggregate is:

[0029] S21, spraying the wastewater from the concrete sedimentation tank onto the surface of the recycled fine aggregate until it is saturated and surface-dry;

[0030] S22, carbonizing and curing the surface-moistened recycled fine aggregate to obtain CO2-enhanced recycled fine aggregate.

[0031] Specifically, in the above step S22, the carbonization curing conditions are: CO2 purity is not less than 99.9%, carbonization temperature is 20±2°C, carbonization relative humidity is not less than 50%, carbonization pressure is 0.1 bar to 0.4 bar, and carbonization time is 20h to 30h.

[0032] In the above step S3, the specific preparation method of the activated regenerated powder is:

[0033] S31, spraying the wastewater from the concrete sedimentation tank onto the surface of the regenerated powder until it is saturated and surface-dry;

[0034] S32, carbonizing and curing the surface-moistened regenerated powder to obtain carbonized regenerated powder;

[0035] S33, subjecting the carbonized regenerated powder to thermal activation treatment to obtain activated regenerated powder.

[0036] Specifically, in the above step S32, the conditions for carbonization curing are: CO2 purity is not less than 99.9%, CO2 concentration is 10% to 30%, carbonization temperature is 60°C to 100°C, and carbonization time is 0.5h to 1h.

[0037] Specifically, in the above step S33, the conditions for thermal activation are: thermal activation temperature is 600° C. to 800° C., and thermal activation time is 60 min to 120 min.

[0038] Furthermore, during the thermal activation process, the heating rate is generally controlled at 5° C. / min to 10° C. / min to reach a preset thermal activation temperature.

[0039] Preferably, in the above step S1, the amount of water used for preliminary dispersion of the regenerated carbon fibers and the dispersant is about 20% to 30% of the total amount of water.

[0040] Compared with the prior art, the present invention has the following significant advantages:

[0041] (1) The alkali-activated all-solid waste-based regenerated mortar provided by the present invention is a low-carbon green regenerated building material, in which the cementitious materials are all solid waste, which can absorb a large amount of construction solid waste resource-based regenerated powder, reduce the dependence of alkali-activated materials on traditional materials - slag and kaolin, and use a synergistic method of waste liquid spraying, carbonization, and thermal activation to treat the regenerated powder, thereby achieving performance improvement of the alkali-activated regenerated powder cementitious material, and the effect of improving its early mechanical properties is particularly significant.

[0042] (2) The present invention is aimed at CO2 enhancement technology for the performance of recycled aggregates, and proposes a pretreatment technology for preparing recycled aggregates (using calcium-rich wastewater from the sedimentation tank of a mixing station), which achieves efficient absorption of CO2 gas by recycled aggregates and improvement of the performance of recycled aggregates, further realizes the recycling of wastewater, and has a significant environmental effect.

[0043] (3) The output of carbon fiber waste is huge and cannot be decomposed, which will cause harm to the environment. In the alkali-activated all-solid waste-based regenerated mortar of the present invention, the recycled carbon fiber is used to prepare the alkali-activated material, which not only helps the volume stability, but also is conducive to the resource utilization of the recycled carbon fiber, with significant environmental and economic effects. DETAILED DESCRIPTION

[0044] The above technical solution of the present invention will be embodied in combination with specific embodiments below. However, those skilled in the art should understand that the following embodiments are only specific examples of the above technical solution and are not intended to limit all of them. Routine adjustments made by those skilled in the art based on common sense are all within the protection scope of this technical solution.

[0045] In the following embodiments, the CO2 enhanced recycled fine aggregate in Embodiments 1, 2 and 5 is obtained by the following process:

[0046] First, spray the wastewater from the concrete sedimentation tank on the surface of the recycled fine aggregate until it is saturated and surface-dry;

[0047] Then, the surface wet recycled fine aggregate is placed in a carbonization curing condition of CO2 purity not less than 99.9%, temperature of 20±2°C, relative humidity of 50%-55%, and pressure of 0.1 bar for 20 hours to obtain CO2 enhanced recycled fine aggregate (continuous gradation with particle size of about 0.15mm-4.75mm).

[0048] The difference between the preparation process of the CO2 enhanced recycled fine aggregate in Examples 3 and 4 and the CO2 enhanced recycled fine aggregate provided in Examples 1, 2 and 5 is that the relative humidity during carbonization curing is 60% to 65%, the pressure is 0.4 bar, and the carbonization time is 30 hours.

[0049] The activated regenerated pulp powder in Example 1 is obtained by the following process:

[0050] First, spray the wastewater from the concrete sedimentation tank onto the surface of the recycled clean slurry powder until it is saturated and surface dry;

[0051] Then, the surface-wetted regenerated clean pulp powder is placed in a CO2 concentration of 10% to 15% (CO2 purity is not less than 99.9%) and a temperature of about 60°C for carbonization curing for 0.5h to obtain carbonized regenerated clean pulp powder;

[0052] Finally, the carbonized regenerated pure pulp powder was subjected to thermal activation treatment at 600° C. for 80 min to obtain activated regenerated pure pulp powder (particle size ≤ 150 μm).

[0053] The difference between the preparation process of the activated regenerated pure pulp powder in Example 2 and the activated regenerated pure pulp powder provided in Example 1 is that the temperature of thermal activation is 800° C. and the time is 60 min.

[0054] The activated recycled concrete powder in Example 3 is obtained by the following process:

[0055] First, spray the wastewater from the concrete sedimentation tank onto the surface of the recycled concrete powder until it is saturated and surface-dry;

[0056] Then, the surface-wetted recycled concrete powder is placed in a CO2 concentration of 25% to 30% (CO2 purity is not less than 99.9%) and a temperature of about 80° C. for carbonization curing for 1 hour to obtain carbonized recycled concrete powder;

[0057] Finally, the carbonized recycled concrete powder was thermally activated at 600°C for 120 min to obtain activated recycled concrete powder (particle size ≤ 75 μm).

[0058] The difference between the preparation process of the activated recycled concrete powder in Example 4 and the activated recycled concrete powder provided in Example 3 is that the temperature of thermal activation is 800° C. and the time is 100 min.

[0059] The activated regenerated mortar powder in Example 5 is obtained by the following process:

[0060] First, spray the wastewater from the concrete sedimentation tank onto the surface of the recycled mortar powder until it is saturated and surface-dry;

[0061] Then, the surface-wetted regenerated mortar powder is placed under the conditions of a CO2 concentration of 20% to 25% and a temperature of 95° C. to 100° C. for carbonization curing for 1 hour to obtain carbonized regenerated mortar powder;

[0062] Finally, the carbonized regenerated mortar powder was subjected to thermal activation treatment at 800° C. for 120 min to obtain activated regenerated mortar powder (particle size ≤ 150 μm).

[0063] The regenerated carbon fibers used in the following embodiments have a length of 6 mm to 18 mm, a diameter of 7 μm to 12 μm, a tensile strength of 1910 MPa to 2200 MPa, and an elongation at break of 2.85% to 3.43%.

[0064] Example 1

[0065] This embodiment provides an early-strength alkali-activated all-solid waste-based regenerated mortar and a preparation method thereof, wherein the preparation steps are as follows:

[0066] 1) 121.08 parts of sodium water glass (modulus is 1.0) and 40.29 parts of sodium hydroxide are uniformly mixed to obtain an alkali activator.

[0067] 2) 2.4 parts of regenerated carbon fiber and 1.8 parts of methyl cellulose were put into 54.10 parts of water for preliminary dispersion, and 1.2 parts of ascorbic acid (analytical grade) were added thereto, and finally an alkali activator was poured in and stirred for secondary dispersion.

[0068] 3) 125.90 parts of water are mixed with 1200 parts of CO2 enhanced recycled fine aggregate so that the surface of the CO2 enhanced recycled fine aggregate is in a wet state.

[0069] 4) Mix 550 parts of activated regenerated pure pulp powder, 40 parts of fly ash and 10 parts of phosphogypsum evenly.

[0070] 5) Add the mixture obtained in step 2) and step 4) into a stirring pot and stir at a low speed for 30 seconds, then add the CO2-enhanced recycled fine aggregate obtained in step 3) into the slurry, stir rapidly for 60 seconds, then add 1.5 parts of sodium lignin sulfonate, stir rapidly for 30 seconds, and obtain alkali-activated all-solid waste-based recycled mortar.

[0071] Example 2

[0072] The similarities between this embodiment and embodiment 1 are not described here, and only the differences from embodiment 1 are described. The difference between this embodiment and embodiment 1 is that: the activated regenerated pure pulp powder in this embodiment is obtained by adopting the above-defined conditions (thermal activation temperature is 800°C, time is 60min); the rest is referred to as described in embodiment 1, and an alkali-activated all-solid waste-based regenerated mortar is provided.

[0073] Example 3

[0074] This embodiment provides an early-strength alkali-activated all-solid waste-based regenerated mortar and a preparation method thereof, wherein the preparation steps are as follows:

[0075] 1) 121.08 parts of sodium water glass (modulus is 1.2) and 40.29 parts of sodium hydroxide are uniformly mixed to obtain an alkaline activator.

[0076] 2) 2.4 parts of regenerated carbon fiber and 1.8 parts of methyl cellulose were put into 54.10 parts of water for preliminary dispersion, and 1.2 parts of ascorbic acid (analytical grade) were added thereto, and finally an alkali activator was poured in and stirred for secondary dispersion.

[0077] 3) 125.90 parts of water are mixed with 1200 parts of CO2 enhanced recycled fine aggregate so that the surface of the CO2 enhanced recycled fine aggregate is in a wet state.

[0078] 4) Mix 550 parts of activated recycled concrete powder, 40 parts of fly ash and 10 parts of phosphogypsum evenly.

[0079] 5) Add the mixture obtained in step 2) and step 4) into a stirring pot and stir at a low speed for 30 seconds, then add the CO2-enhanced recycled fine aggregate obtained in step 3) into the slurry, stir rapidly for 60 seconds, then add 1.5 parts of sodium lignin sulfonate, stir rapidly for 30 seconds, and obtain alkali-activated all-solid waste-based recycled mortar.

[0080] Example 4

[0081] The similarities between this embodiment and embodiment 3 are not described here, and only the differences from embodiment 3 are described. The difference between this embodiment and embodiment 3 is that: in this embodiment, the activated recycled concrete powder is obtained using the above-defined conditions (thermal activation temperature is 800° C., time is 100 min); the rest is referred to in embodiment 3, and an alkali-activated all-solid waste-based recycled mortar is provided.

[0082] Example 5

[0083] This embodiment provides an early-strength alkali-activated all-solid waste-based regenerated mortar and a preparation method thereof, wherein the preparation steps are as follows:

[0084] 1) 1.0 part of regenerated carbon fiber and 0.8 part of methyl cellulose were put into 30 parts of water for preliminary dispersion, 2.4 parts of ascorbic acid (analytical grade) were added thereto, and finally 142 parts of potassium water glass were poured in and stirred for secondary dispersion.

[0085] 2) Mix 120 parts of water with 600 parts of CO2 enhanced recycled fine aggregate so that the surface of the CO2 enhanced recycled fine aggregate is in a wet state.

[0086] 3) Mix 600 parts of activated regenerated mortar powder, 5 parts of fly ash and 20 parts of phosphogypsum evenly.

[0087] 4) Add the mixture obtained in step 1) and step 3) into a stirring pot and stir at a low speed for 30 seconds, then add the CO2-enhanced recycled fine aggregate obtained in step 2) into the slurry, stir rapidly for 60 seconds, then add 0.5 parts of sodium lignin sulfonate, stir rapidly for 30 seconds, and obtain alkali-activated all-solid waste-based recycled mortar.

[0088] In order to demonstrate the importance of the activated regenerated powder component in the above-mentioned alkali-activated all-solid waste-based regenerated mortar of the present invention (especially its treatment process), the following comparative experiment was carried out.

[0089] Comparative Example 1

[0090] This comparative example is intended to illustrate the advantages of activated recycled concrete powder over ordinary recycled concrete powder that has not been activated.

[0091] The similarities between this comparative example and Examples 3 and 4 are not described here, and only the differences from Examples 3 and 4 are described. The difference between this comparative example and Examples 3 and 4 is that an equal amount of ordinary recycled concrete powder without any activation treatment is used in this comparative example to replace the activated recycled concrete powder in Examples 3 and 4; the rest is referred to as described in Examples 3 and 4, and a comparative alkali-activated all-solid waste-based recycled mortar is provided.

[0092] Comparative Example 2

[0093] This comparative example is intended to illustrate the advantages of activated regenerated pure pulp powder over ordinary regenerated pure pulp powder that has not been activated.

[0094] The similarities between this comparative example and Examples 1 and 2 are not described here, and only the differences from Examples 1 and 2 are described. The difference between this comparative example and Examples 1 and 2 is that an equal amount of ordinary regenerated pure pulp powder without any activation treatment is used in this comparative example to replace the activated regenerated pure pulp powder in Examples 1 and 2; the rest is referred to as described in Examples 1 and 2, and a comparative alkali-activated all-solid waste-based regenerated mortar is provided.

[0095] Comparative Example 3

[0096] This comparative example is intended to illustrate the influence of thermal activation temperature on the activation effect in the treatment process of activated recycled concrete powder.

[0097] The similarities between this comparative example and Example 3 are not described here, and only the differences from Example 3 are described. The difference between this comparative example and Example 3 is that an equal amount of comparative activated recycled concrete powder is used in this comparative example to replace the activated recycled concrete powder in Example 3, that is, the thermal activation temperature of the comparative activated recycled concrete powder in this comparative example is 400°C; the rest is referred to as described in Example 3, and a comparative alkali-activated all-solid waste-based recycled mortar is provided.

[0098] Comparative Example 4

[0099] This comparative example is intended to illustrate the influence of thermal activation operation on the activation effect of the treatment process of activated recycled concrete powder.

[0100] The similarities between this comparative example and Example 3 are not described here, and only the differences from Example 3 are described. The difference between this comparative example and Example 3 is that in this comparative example, an equal amount of non-thermally activated recycled concrete powder is used to replace the activated recycled concrete powder in Example 3, that is, the non-thermally activated recycled concrete powder in this comparative example is only subjected to waste liquid spraying and carbonization, but not thermal activation treatment; the rest is referred to as described in Example 3, and a comparative alkali-activated all-solid waste-based recycled mortar is provided.

[0101] Comparative Example 5

[0102] This comparative example is intended to illustrate the effect of direct thermal activation (lack of waste liquid spraying and carbonization) on the activation effect of the treatment process of activated recycled concrete powder.

[0103] The similarities between this comparative example and Example 3 are not described here, and only the differences from Example 3 are described. The difference between this comparative example and Example 3 is that in this comparative example, an equal amount of heat-activated recycled concrete powder is used to replace the activated recycled concrete powder in Example 3, that is, the heat-activated recycled concrete powder in this comparative example is not sprayed with waste liquid and carbonized, but directly subjected to heat activation treatment; the rest is referred to as described in Example 3, and a comparative alkali-activated all-solid waste-based recycled mortar is provided.

[0104] The data on the compressive strength of the alkali-activated all-solid waste-based regenerated mortar at different ages provided in the above-mentioned embodiments and comparative examples are shown in Table 1 below.

[0105] Table 1 Compressive strength of alkali-activated all-solid waste-based regenerated mortar provided in each embodiment and comparative example

[0106]

[0107] As can be seen from Table 1, whether comparing Comparative Example 1 with Examples 3 and 4, or comparing Comparative Example 2 with Examples 1 and 2, it is found that the 1d strength data of the alkali-activated all-solid waste-based regenerated mortar using activated regenerated powder has increased significantly, showing early strength characteristics. This is because if the regenerated powder is not activated, the recycled concrete powder, recycled slurry powder, etc. are prepared from construction waste, which contain a large amount of inert substances such as silicon dioxide and calcium carbonate, and the effect of being stimulated by the alkali activator in the corresponding system is limited.

[0108] Comparing Comparative Example 3 and Example 3, if a lower temperature is used to thermally activate the regenerated powder after waste liquid spraying and carbonization, the regenerated concrete powder contains a large amount of calcium carbonate and a small amount of calcium hydroxide. When the thermal activation temperature is low (400°C), calcium carbonate and calcium hydroxide do not decompose, and the effect on the decomposition and reorganization of the entire component of the regenerated concrete is limited. That is, the activity of the activated regenerated concrete powder is low, which further leads to poor excitation effect of the alkali activator.

[0109] Comparing Comparative Example 4 and Example 3, if the recycled concrete powder is only subjected to waste liquid spraying and carbonization without thermal activation treatment, a certain amount of calcium carbonate with poor crystallinity will be produced in the recycled concrete powder due to the waste liquid spraying and carbonization, but generally speaking, its components are mostly inert substances, and the alkali activator cannot fully stimulate its activity, that is, the activity exhibited by the non-thermally activated recycled concrete powder is still relatively low.

[0110] Comparing Comparative Example 5 and Example 3, if the recycled concrete powder is directly subjected to high-temperature thermal activation treatment, the calcium carbonate and some small amounts of hydration products in the recycled concrete powder will decompose after high-temperature calcination, but the large amount of calcium carbonate with very good crystallization will not necessarily be completely decomposed to form CaO under the action of high temperature, and the degree of dissolution and participation in the polymerization reaction under the action of the alkali activator in the corresponding system is also correspondingly low, that is, a single thermal activation still cannot make the recycled powder show excellent activity.

[0111] In summary, for the modifications under the conditions of the above-mentioned comparative examples 3 to 5, the corresponding treated regenerated powders cannot exhibit excellent activity, and the corresponding alkali-activated all-solid waste-based regenerated mortars obtained not only perform poorly in compressive strength, but also perform worse in 1d compressive strength, and cannot show the excellent characteristics of early strength.

Claims

1. An early-strength alkali-activated all-solid waste-based regeneration mortar, characterized in that: It comprises the following components mixed uniformly: 550~600 parts of activated regenerated powder; 600~1200 parts of CO2-enhanced recycled fine aggregate; 5~40 parts of fly ash; 10-20 parts of phosphogypsum; 1~2.4 parts of recycled carbon fiber; 140-165 parts of alkali activator; Water reducing agent 0.5~1.5 parts; Retarder 1.2~2.4 parts; Dispersant 0.8~1.8 parts; 150~180 parts of water; The activated regenerated powder is a powder with a particle size not exceeding 150 μm obtained by spraying and soaking the regenerated powder with wastewater from a concrete sedimentation tank, carbonizing and curing the regenerated powder, and then thermally activating the powder; wherein the thermal activation conditions are: the thermal activation temperature is 600° C. to 800° C., and the thermal activation time is 60 min to 120 min; The CO2 enhanced recycled fine aggregate is a continuously graded particle with a particle size of 0.15 mm to 5 mm obtained by spraying and soaking the recycled fine aggregate with wastewater from a concrete sedimentation tank and then carbonizing and curing; The water reducing agent is sodium lignin sulfonate; and the dispersant is methyl cellulose.

2. The early-strength alkali-activated all-solid waste-based regenerated mortar according to claim 1, characterized in that: The regenerated powder includes at least one of regenerated concrete powder, regenerated mortar powder and regenerated paste powder.

3. The early-strength alkali-activated all-solid waste-based regenerated mortar according to claim 1, characterized in that: The regenerated carbon fiber is waste fiber generated in the process of producing carbon fiber or carbon fiber extracted from waste.

4. The early-strength alkali-activated all-solid waste-based regenerated mortar according to claim 3, characterized in that: The length of the regenerated carbon fiber is 6 mm to 18 mm, the diameter is 7 μm to 12 μm, the tensile strength is 1910 MPa to 2200 MPa, and the elongation at break is 2.85% to 3.43%.

5. The early-strength alkali-activated all-solid waste-based regenerated mortar according to claim 1, characterized in that: The alkaline activator is selected from at least one of potassium water glass, sodium water glass and sodium hydroxide; and the retarder is ascorbic acid.

6. A method for preparing an early-strength alkali-activated all-solid waste-based regenerated mortar as claimed in any one of claims 1 to 5, characterized in that: Includes steps: S1. Preliminarily dispersing the regenerated carbon fiber and the dispersant in part of the water, and then sequentially adding a retarder and an alkali activator thereto for secondary dispersion to obtain a mixed functional component; S2, stirring the remaining water with the CO2 enhanced recycled fine aggregate, so that the surface of the CO2 enhanced recycled fine aggregate is in a wet state; S3, mixing the activated regenerated powder with fly ash and phosphogypsum to obtain a mixed powder; S4. Fully stir the mixed functional components and the mixed powder, add the moistened CO2-strengthened recycled fine aggregate thereto, and add a water reducer, and mix them thoroughly to obtain the early-strength alkali-activated all-solid waste-based recycled mortar.

7. The preparation method according to claim 6, characterized in that: In step S2, the specific preparation method of the CO2 enhanced recycled fine aggregate is: S21, spraying the wastewater from the concrete sedimentation tank onto the surface of the recycled fine aggregate until it is saturated and surface-dry; S22, carbonizing and curing the surface-moistened recycled fine aggregate to obtain the CO2-enhanced recycled fine aggregate; Among them, the conditions for carbonization curing are: CO2 purity is not less than 99.9%, carbonization temperature is 20±2℃, carbonization relative humidity is not less than 50%, carbonization pressure is 0.1 bar~0.4 bar, and carbonization time is 20 h~30 h.

8. The preparation method according to claim 6, characterized in that: In step S3, the specific preparation method of the activated regenerated powder is: S31, spraying the wastewater from the concrete sedimentation tank onto the surface of the regenerated powder until it is saturated and surface-dry; S32, carbonizing and curing the surface-moistened regenerated powder to obtain carbonized regenerated powder; Among them, the conditions for carbonization curing are: CO2 purity not less than 99.9%, CO2 concentration 10%~30%, carbonization temperature 60℃~100℃, carbonization time 0.5h~1h; S33, subjecting the carbonized regenerated powder to thermal activation treatment to obtain the activated regenerated powder; Among them, the conditions of thermal activation are: thermal activation temperature is 600℃~800℃, and thermal activation time is 60 min~120 min.

9. The preparation method according to any one of claims 6 to 8, characterized in that: In step S1, the amount of water used to preliminarily disperse the regenerated carbon fiber and the dispersant is 20% to 30% of the total amount of water.

Citation Information

Patent Citations

  • Method for reinforcing recycled concrete fine aggregate by using carbon dioxide

    CN105174766A

  • Recycled concrete block prepared from CO2 reinforced recycled powder

    CN112028564A

  • Alkali-activated regenerated micro-powder foam concrete and preparation method thereof

    CN112062533A